1984
DOI: 10.1203/00006450-198409000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Maternal Metabolism Throughout Pregnancy in the Conscious Rabbit

Abstract: SummaryStudies of maternal metabolism during pregnancy have focused principally upon the latter half of gestation. However, maternal metabolic adaptations to pregnancy may occur at all stages of pregnancy. To study maternal metabolism throughout pregnancy, we developed a chronically catheterized rabbit model in which animals could be studied under conscious, stress-free conditions when nonpregnant and then serially throughout pregnancy.Anesthesia produced marked hyperglycemia. In contrast, chronic catheterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…Elevated maternal plasma levels of chorionic gonadotrophin that increase in late pregnancy in sheep also may add to the inhibition of glucose utilization (10, 1 1). Similar changes in hormonal milieu have been observed in late pregnancy in human (3), rat (7), and rabbit (29) and have been associated with both glucose intolerance and insulin resistance. In the present study, sheep appear to be similar in that high levels of insulin can enhance tissue glucose utilization but to a lesser extent than in nonpregnant fed ewes, indicating that the mechanisms producing the reduced basal glucose utilization rate of the nonuterine tissues in sheep cannot be reversed easily with insulin (at least at the levels and duration achieved in the present study).…”
mentioning
confidence: 53%
“…Elevated maternal plasma levels of chorionic gonadotrophin that increase in late pregnancy in sheep also may add to the inhibition of glucose utilization (10, 1 1). Similar changes in hormonal milieu have been observed in late pregnancy in human (3), rat (7), and rabbit (29) and have been associated with both glucose intolerance and insulin resistance. In the present study, sheep appear to be similar in that high levels of insulin can enhance tissue glucose utilization but to a lesser extent than in nonpregnant fed ewes, indicating that the mechanisms producing the reduced basal glucose utilization rate of the nonuterine tissues in sheep cannot be reversed easily with insulin (at least at the levels and duration achieved in the present study).…”
mentioning
confidence: 53%
“…Because the rabbits used in the present study were relatively young at the time of mating (16)(17)(18) (59) by affecting bone-specific ALP (15,47). Estrogen (estradiol) levels in pregnant rabbits have been reported to increase during the first 7 days after mating (28) and then remain relatively stable until the last 2-3 days before parturition, when a small increase occurs (8,18).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples from 90 nulliparous, nonpregnant New Zealand White rabbits (ages [16][17][18] wk) were drawn at the supplier's facility (Centre Lago, Vonnas, France). These samples were used to create the pretest database against which values recorded during pregnancy were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…rabbit f5], guinea-pig f6], human j4,7f and rat [8-l 11, either in the ~stabsorptive state or after an overnight fast. Hence, it has been suggested that gluconeogenesis decreases in the fed pregnant animal during late gestation [5,12,13]. However, we have recently shown that the in vivo rates of gluconeogenes~s from lactate increase &fold in fed pregnant rats at term gestation [14], which represents almost 50% of the glucose utilized by the conceptus [10,14], Nevertheless, decreased operation of the glucose-alanine cycle has been reported to occur in late pregnancy [IS].…”
Section: Introductionmentioning
confidence: 99%